Constructing Playful Talk through Translanguaging in English Medium Instruction Mathematics Classrooms - Tai, Kevin W H; Wei, Li (Applied linguistics, 2021)
Abstract Recent studies on English-Medium-Instruction (EMI) classroom interaction have begun to look at the role of translanguaging as a pedagogical practice in supporting participants to exploit multilingual and multimodal resources to facilitate content teaching and learning. The present study contributes to this growing body of literature by focusing on playful talk in multiple languages and modalities in EMI mathematics classrooms in a secondary school in Hong Kong. Based on the data collected from a linguistic ethnography, we analyze how the teacher constructs playful talk in order to achieve various pedagogical goals including building rapport, facilitating content explanation and promoting meaningful communication with students. The analysis demonstrates that translanguaging appears to be a critical resource and that several social factors, including the teacher’s personal belief, history, sociocultural, and pedagogical knowledge, play a role in constructing playful talk. The playful talk transforms the classroom into a translanguaging space, which in turn allows the teacher and students to perform a range of creative acts and experiment with a variety of voices to facilitate the meaning making and knowledge construction processes.